Clinical application of multi-direction temporary Kapandji technique and volar locking plate fixation for type C distal radius fractures - Wei Zhao; Kun-xiu Song; Yong-tao Liu; Bing-dong Ma (BMC Surgery)
Abstract Purpose Achieving and maintaining an optimal reduction in partially or fully displaced intra-articular fractures, specifically Type C distal radius fractures, can present challenges. This study aims to retrospectively evaluate and summarize a method utilizing multi-directional temporary Kapandji technique in combination with the volar locking plate fixation for these fractures. Method The study involved 15 patients diagnosed with Type C distal radius fractures who underwent surgery between January 2024 and April 2024. The procedure incorporated a multi-directional temporary Kapandji technique, followed by stable osteosynthesis using a volar locking plate system. The functional outcomes were assessed after 4 (2–6) months of follow-up using the modified Mayo wrist scoring system (MMWS). The MMWS is a rating system used to evaluate wrist function and pain, including pain, motion, grip strength. Results All the patients incision healed within 2 weeks. All the fractures had uneventful union within 8–12 weeks. Based on the modified Mayo wrist scoring (MMWS) system, most patients showed good to excellent functional recovery. Conclusion This reduction method proved to be both simple and replicable, enabling satisfactory alignment with minimal force. The volar locking plate system provided rigid and stable fixation.